Development and evaluation of stimulus-sensitive microgels for controlled drug delivery. Issue 3 (15th September 2020) - Qureshi, Umbreen Fatima; Rasool, Muhammad Fawad; Ranjha, Nazar Muhammad; Majeed, Abul
Abstract : The novelty of the present work was focused on the synthesis of pH- and temperature-responsive cross-linked poly(methacrylic acid- co -acrylamide) (p(MAA- co -AM)) microgels for controlled drug delivery. A series of cross-linked microgels was successfully prepared by inverse-suspension polymerization using N, N ′-methylenebisacrylamide as a cross-linking agent and potassium persulfate as an initiator. The swelling of the microgels was investigated as a function of pH (2.1 and 7.4) and temperature (20–50°C). The prepared microgels were characterized by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry, X-ray diffraction, thermogravimetric analysis, scanning electron microscopy (SEM), particle size analysis and drug-release behavior analysis. FTIR and thermal studies confirmed the formation of a new cross-linked p(MAA- co -AM) polymer. SEM revealed that the microgels were made of spherical, slightly rough and cross-linked particles. To study the controlled-drug-release behavior of microgels, captopril was successfully loaded as a model drug by using an in situ method. The maximum in vitro drug release was up to 96 and 55% at pH 7.4 and 2.1, respectively. All formulations showed pH-dependent drug release following the Higuchi model of drug-release mechanism. In light of the results obtained from the study, it was concluded that p(MAA- co -AM) microgels have potential applications in release of drugs in a controlled manner with respect to pH and temperature.